2005
DOI: 10.1111/j.1462-2920.2005.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of nascent, deep‐sea hydrothermal vents by a novel Archaeal and Nanoarchaeal assemblage

Abstract: Active deep-sea hydrothermal vents are areas of intense mixing and severe thermal and chemical gradients, fostering a biotope rich in novel hyperthermophilic microorganisms and metabolic pathways. The goal of this study was to identify the earliest archaeal colonizers of nascent hydrothermal chimneys, organisms that may be previously uncharacterized as they are quickly replaced by a more stable climax community. During expeditions in 2001 and 2002 to the hydrothermal vents of the East Pacific Rise (EPR) (9 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 37 publications
3
66
0
1
Order By: Relevance
“…To date, microbial communities in nascent and mature hydrothermal deposits of active vents have been well studied (1,36,52,56,57,63,68,70,72). However, microbial communities in sulfide structures of inactive vents are poorly understood (65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, microbial communities in nascent and mature hydrothermal deposits of active vents have been well studied (1,36,52,56,57,63,68,70,72). However, microbial communities in sulfide structures of inactive vents are poorly understood (65).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolically and phylogenetically diverse chemolithoautotrophs thrive within the sulfide structures of active vents using chemical energy provided from redox reactions between reductants (e.g., H 2 , H 2 S, CH 4 , and Fe 2ϩ ) in the vent fluids and oxidants (e.g., O 2 , NO 3 Ϫ , and SO 4 2Ϫ ) in the surrounding seawater (53). The diversity and abundance of microbial communities in active vent structures have been reported (36,52,54,56,63,67,68,70,72). However, little is known about the microbial communities in sulfide structures of inactive vents with the exception of one report (65): whether and how the abundance, diversity, and composition of microbial communities within the sulfide structures change after hydrothermal activity ceases in deep-sea vent fields is currently unclear.…”
mentioning
confidence: 99%
“…For example, in one study conducted at 13°N at East Pacific Rise, heterotrophic microorganisms were the first colonizers of a newly formed chimney structure, followed by in-growth of chemolithoautotrophs (408), whereas autrotrophs were the first colonizers of chimneys formed over a vent at the MidAtlantic Ridge (467). In a colonization experiment at chimneys with different ages, chemolithoautotrophic archaea related to Ignicoccus organisms and their Nanoarchaeum symbionts dominated the initial colonization of high-temperature chimneys, whereas heterotrophs related to Thermococcales were more abundant at mature vents (358). This study supports the hypothesis that initial chimney colonizers are autotrophic, being replaced or joined by heterotrophs within days to hours of chimney formation.…”
Section: Vol 75 2011 Microbial Ecology Of the Dark Ocean 389mentioning
confidence: 99%
“…Recent studies have demonstrated that microbial diversity varied from vent to vent and from days to years within the same vent field (6,7). The unique mineralogical and chemical compositions of a chimney in the early stages of its formation may support a distinct pioneering microbial community (8,9). By analyzing the conserved specific functional genes (such as nifH and mcrA), the metabolic diversity of some specific organisms in the mature chimneys was partially investigated (10,11).…”
mentioning
confidence: 99%